Cryotechnology in lung and heart-lung transplantation - M. T. Bekov; I. V. Pashkov; N. P. Mozheiko; R. A. Latypov; D. O. Oleshkevich; K. S. Smirnov; E. F. Shigaev; Ya. S. Yakunin; S. V. Gautier (Вестник трансплантологии и искусственных органов)
Bronchial complications, along with development and progression of chronic dysfunction on the background of chronic rejection, are factors that reduce the quality and life of lung and heart-lung recipients. They also increase the frequency of hospitalizations. Application of cryotechnology is based on the contact effect of extremely low temperatures on organs and tissues using a cryoprobe. This article demonstrates the experience of using cryotechnology in the diagnosis and treatment of complications in lung and heart-lung recipients.